Pricing GHG emissions in agriculture: Accounting for trade and fairness for effective climate policy - Mattia Ricci; Ignacio Pérez Domínguez; Jordan Hristov; Toon Vandyck; Stijn Van Houtven (European Commission, Joint Research Centre (JRC), 2024)
Although agriculture is an important source of greenhouse gas emissions, the sector remains out of scope for greenhouse gas (GHG) pricing policies. To align the future food system with the transition to net zero emissions, two key questions arise: To what extent can tax policies help achieving this transition in a fair and effective way? And, would it be preferable to levy a GHG tax on the production or the consumption side? We employ an EU agro-economic model to compare production and consumption-side GHG taxes and to quantify their environmental impact. We find that supply-side pricing in agriculture displays leakage rates of over 40% and leaves EU producers in a situation of competitive disadvantage; on the other hand, demand-side measures level the playing field in the Single Market and generate positive leakage as they boost the export of (greener) EU producers. Focussing on four countries - Spain, France, Romania and Poland - we therefore consider a real-world reform based on adjusting Value-Added Taxes to reflect climate change externalities. Using microsimulation techniques and household-level data we show that - while this reform can generate reductions in emissions - is regressive without complementary measures. Feebate and equal-per-capita revenue recycling address equity concerns and produce welfare gains for the majority of the population, while the top 20-30% of meat consumers experiences welfare losses. Overall, findings suggest that price-based measures can help align agriculture with climate goals but trade and equity aspects should be reflected in policy design.
Keywords: D6; H2; Q1; Q5; 330; climate policies; food system; VAT reform; fairness